Meta-analysis of acupuncture combined therapies for amblyopia: efficacy and safety insights - Tan, Kang; Yu, Yunfeng; Liu, Pei; Jiang, Pengfei; Liu, Yi; Lou, Bidan; Peng, Qinghua (Frontiers in Medicine, 2025)
BackgroundAcupuncture, a traditional Chinese medicine therapy, is widely used for the management of amblyopia. This study aimed to perform a meta-analysis of the efficacy and safety of acupuncture combined with conventional treatments for amblyopia.MethodsWe searched eight databases for relevant studies published before December 31, 2024. Subsequently, the retrieved literature underwent a rigorous screening process based on pre-established inclusion and exclusion criteria. Thereafter, the basic information, outcome data, and risk of bias of the included studies were statistically analyzed. RevMan5.3 was employed to perform meta-analysis, sensitivity analysis, and assessment of publication bias. Additionally, GRADEpro3.6 was utilized to assess the quality of evidence for the outcomes.ResultsTen trials involving 918 eyes were included. The meta-analysis demonstrated that, compared with to the conventional treatment, the acupuncture combined with conventional treatment significantly improved the clinical efficacy rate (relative risk [RR] 1.31, 95% confidence interval [CI] 1.21–1.43, P < 0.00001, GRADE: low), the best-corrected visual acuity (BCVA) [mean difference (MD) 0.08, 95% CI 0.01–0.15, P = 0.03, GRADE: very low], and the amplitude of pattern visual evoked potential (P-VEP) P100 wave (MD 3.24, 95% CI 1.42–5.05, P = 0.0005, GRADE: low), while reduced the stereoacuity (MD −3.59, 95% CI −5.97 to 1.20, P = 0.003, GRADE: very low) and the latency of P-VEP P100 wave (MD −7.44, 95% CI −11.71 to −3.18, P = 0.0006, GRADE: very low). However, acupuncture may increase the adverse reaction rate (RR 5.57, 95% CI 1.01–30.84, P = 0.05, GRADE: low). Funnel plots indicated no publication bias in the clinical efficacy rate, latency of P-VEP P100 wave, amplitude of P-VEP P100 wave, or adverse events. Nevertheless, potential publication bias was detected for BCVA and stereoacuity.ConclusionCompared to conventional treatment, acupuncture combined with conventional treatment effectively improved visual acuity in amblyopia patients, although it may increase the risk of adverse events. Considering that these adverse events are mild, acupuncture still has the potential to serve as a complementary treatment for amblyopia. However, these findings need to be further validated through large-scale and high-quality studies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251063432, identifier CRD420251063432.